Impact of parental migration on psychosocial well-being of children left behind: a qualitative study in rural China - Chenyue Zhao; Feng Wang; Xudong Zhou; Minmin Jiang; Therese Hesketh (International Journal for Equity in Health, 2018)
Abstract Background Tens of millions of rural “left-behind children (LBC)” in China grow up experiencing prolonged separation from their migrant worker parents. This study aimed to explore how children are affected by parental migration, from the perspectives of children, parents, and grandparents, focusing on the experiences of prolonged parent-child separation and relationship dynamics in the extended family. Methods Qualitative in-depth interviews were conducted in a migrant-sending rural area of eastern China. Participants included 25 children (aged 7 to 14), 17 parents, and 13 grandparents, from 30 families, as well as 24 key informants from the communities. Data analysis followed a grounded theory approach. Results The results showed that despite the original purpose of benefiting children, parental migration resulted in challenges in child psychosocial well-being, due to the emotional impacts from prolonged parent-child separation. Parental absence also led to inadequate care and support for left-behind children. The negative effects of parental migration may be exacerbated by other vulnerabilities such as parents’ divorce, poverty and grandparent caregivers’ frailty. Concerns about child well-being made some migrants decide to return home permanently, because of the altered trade-offs of migration. Conclusion Prolonged separation following migration often disrupts parent-child relationships and results in psychosocial difficulties in LBC, especially among those who live with multiple adversities in the family. Community-based interventions may help migrant parents and co-resident caregivers to better engage children and promote their resilience.